P03.02 A mutated prostatic acid phosphatase (PAP) peptide-based vaccine induces PAP-specific CD8+ T cells with ex vivo cytotoxic capacities in HHDII/DR1 transgenic mice. (21st September 2022) - Thomas, JE; McArdle, S; Christensen, D; LeVu, P
Abstract : Background: Prostate cancer (PCa) is the second most frequent cancer in men and the fifth most frequent cause of cancer-related deaths in men worldwide. Current treatments for castrate (hormone)-resistant prostate cancer (CRPC) are limited and not curative, with a median survival from diagnosis of 23 months. Sipuleucel-T is the only FDA approved autologous cellular immunotherapy for PCa targeting prostatic acid phosphatase (PAP), showing a 4.1 month survival benefit for metastatic castration-resistant prostate cancer patients. However, its anti-neoplastic responses remain minimal and is cost prohibitive and while PAP is a good target for future prostate cancer vaccine, new, more affordable therapeutic approaches are therefore needed to treat advanced PCa. We have previously shown that a 15 amino acid (AA) PAP sequence-derived peptide could induce strong immune responses and delay the growth of murine TRAMP-C1 prostate tumours. We have now substituted one amino acid and elongated the sequence to include epitopes predicted to bind to several additional HLA haplotypes. Herein, we present the immunological properties of this 42mer-mutated PAP-derived sequence (MutPAP42mer) and the additional use of another PAP-derived sequence of 15 AA long to increase the CD4 + T-cell responses. Materials and Methods: The presence of PAP-135–143 epitope-specific CD8+ T cells in the blood of patients with prostate cancer (PCa) was assessed by flow cytometry using Dextramer™ technology. HHDII/DR1 transgenic mice were immunized with mutated and non-mutated PAP-derived 42mer peptides in the presence of CAF®09 or CpG ODN1826 or 2395 (TLR-9 agonist) adjuvants. WT-hPAP-42mer was also used to immunise syngeneic C57Bl/6 mice. Vaccine-induced immune responses were measured by assessing the proportion and functionality of splenic PAP-specific T cells in vitro. Results: PAP-135–143 epitope-specific CD8+ T cells were detected in the blood of patients with PCa and stimulation of PBMCs from patients with PCa with mutPAP42mer enhanced their capacity to kill human LNCaP PCa target cells expressing PAP. MutPAP42mer peptide was significantly more immunogenic in HHDII/DR1 mice than the wild type sequence, and immunogenicity was further enhanced when combined with the CAF09b® adjuvant. The vaccine induced secretory (IFNγ and TNFα) and cytotoxic CD8+ T cells and effector memory splenic T cells. Conclusions: The periphery of patients with PCa exhibits immune responsiveness to the MutPAP42mer peptide and immunization of mice induces/expands T cell-driven, wild-type PAP immunity, and therefore, has the potential to drive protective anti-tumour immunity in patients with PCa. Disclosure Information: J.E. Thomas: None. S. McArdle: None. D. Christensen: None. P. LeVu: None.